ChemInform Abstract: Cross‐Dehydrogenative Coupling of Tertiary Amines and Terminal Alkynes Catalyzed by Copper Nanoparticles on Zeolite. Issue 13 (March 2016) - Alonso, Francisco; Arroyo, Adrian; Martin‐Garcia, Iris; Moglie, Yanina
Abstract: Oxidized copper nanoparticles on sodium Y zeolite are used as a novel heterogeneous catalyst for the cross‐dehydrogenative coupling of tertiary amines and terminal alkynes.